2019
DOI: 10.1038/s41598-019-39330-y
|View full text |Cite
|
Sign up to set email alerts
|

A new model for predicting intravenous immunoglobin-resistant Kawasaki disease in Chongqing: a retrospective study on 5277 patients

Abstract: Accurate evaluation of individual risk of intravenous immunoglobin (IVIG)-resistance is critical for adopting regimens for the first treatment and prevention of coronary artery lesions (CALs) in patients with Kawasaki disease (KD). Methods: The KD patients hospitalized in Chongqing Children’s Hospital, in west China, from October 2007 to December 2017 were retrospectively reviewed. Data were collected and compared between IVIG-resistant group and IVIG-responsive group. The independent risk factors were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 33 publications
5
32
0
1
Order By: Relevance
“…If there is significant heterogeneity among studies, addition or reduction of any one study may lead to remarkable change in results, so we used sensitivity analysis to verify the reliability of the meta-analysis findings. In addition to the discovery that Tan's study (31) had a great impact on pooled effect in the metaanalysis of ESR as shown in Figure 10 (The ESR data of this study was omitted in this meta-analysis), there was no significant change in the pooled OR and WMD after every single study was omitted, this indicated that our results were convinced because of good stability and not driving by any single study.…”
Section: Sensitivity Analysismentioning
confidence: 68%
“…If there is significant heterogeneity among studies, addition or reduction of any one study may lead to remarkable change in results, so we used sensitivity analysis to verify the reliability of the meta-analysis findings. In addition to the discovery that Tan's study (31) had a great impact on pooled effect in the metaanalysis of ESR as shown in Figure 10 (The ESR data of this study was omitted in this meta-analysis), there was no significant change in the pooled OR and WMD after every single study was omitted, this indicated that our results were convinced because of good stability and not driving by any single study.…”
Section: Sensitivity Analysismentioning
confidence: 68%
“…In this study, not only FC levels but also T-Bil, AST, and ALT level were associated with unresponsiveness to IVIG. Previous studies have shown that these values were higher in non-responders than in responders [20,21,22]. It is remarkable that all these factors have also been incorporated into the existing refractory prediction scores, such as Osaka, Kurume, and Gumma scores [7,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Several scoring systems (6)(7)(8)(9)(10)(11)(12) have been proposed. However, the predictive capacity of the existing scoring systems may not be sufficient, and some scoring systems have poor predictive performance for external datasets (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%